Centro deportivo de alto rendimiento Ibagué la musical (2020)
In the city of Ibagué, the sports equipment for the practice of extreme sports ended its existence some time ago, the absence of the stage of the sports park has caused much controversy, including a deficiency of spaces for adequate training in athletes , an urban-environmental imbalance in the city, affecting the environment and the quality of life of the population of the commune 8. However, the intervention area where the urban and architectural proposal is proposed, has a shortage of public space, areas green and the lack of an appropriate road system. That is why it is proposed to design a high-performance sports center for extreme and alternative sports, spaces such as skateboards, bmx and roller, together with an environmental axis, generating an integration between the institutional equipment and the proposal urban, so that the sectors are articulated and connected from elevated roads (bridges), recreation areas, in addition to relocating homes, improving public space for the inhabitants of the Ciudadela Simón Bolívar neighborhood stage I and II. A methodological process is presented, which addresses the deductive method, where the sector is contemplated, analyzing and observing physical and social factors such as: crime, insecurity that occur in the area. Then it continues with the Second phase, the inductive method, which is carried out a study in order to find an architectural and urban solution based on the investigation of documents, cartographies, references and regulations (POT) applied in the city to guarantee the feasibility in the project.